Clinical and aetiological study of adenoviral conjunctivitis, with special reference to adenovirus types 4 and 19 infections. Issue 12 (December 1982) - Aoki, K; Kato, M; Ohtsuka, H; Ishii, K; Nakazono, N; Sawada, H
Abstract : The clinical and aetiological findings are presented on 343 patients with clinical adenoviral conjunctivitis treated between July 1979 and July 1980 at 3 eye clinics in Sapporo. The age of the patients ranged from 12 days to 79 years, and the monthly incidence of the disease from 9 to 83, with clustering in the summer season. The aetiological diagnosis was established in 196 (57%) of 343 patients: adenovirus 3 in 24 cases; adenovirus 4 in 33 cases, including one case serologically diagnosed; adenovirus 8 in 124 cases; and adenovirus 19 in 15 cases. The different serotypes caused different clinical pictures. Adenovirus 19 conjunctivitis was more severe, with keratitis and preauricular lymphadenopathy more frequent than that of adenovirus 3 conjunctivitis. Adenovirus 4 conjunctivitis was generally similar to adenovirus 3 conjunctivitis. The clinical difference between the 2 groups adenoviruses 3 and 4, and adenoviruses 8 and 9, was statistically significant. Although in Japan adenovirus 8 was the most prevalent, adenoviruses 4 and 19 should be considered as causative agents of adenoviral conjunctivitis.